Uptake and Perceptions of E-cigarette use in Vascular Patients. (16th May 2018) - Taylor, Rachael; Sidloff, David; Sayers, Robert D.; Bown, Matthew J.; Saratzis, Athanasios
Abstract : Introduction: Smoking is one of the most important risk factors for cardiovascular disease (CVD). Electronic cigarettes (e-cigarettes) are becoming increasingly popular. However, little is known regarding their patterns of use in patients with established CVD. Aims: We aimed to assess the perceptions and patterns of use of e-cigarettes in patients presenting to a vascular clinic. Methods: We performed a qualitative study to identify perceptions and beliefs about e-cigarettes. Semi-structured interviews of consecutive patients consenting to participate were performed over five-months. Individuals were recruited from a vascular surgery outpatient clinic. Initial interviews were based on a questionnaire. Further structured interviews were conducted with patients currently using e-cigarettes, which were transcribed and analysed to assess perceptions and patterns of use. Results/Findings: Four overarching themes emerged: attraction to e-cigarettes as a harm reduction/smoking cessation strategy; uncertainty regarding the risks of e-cigarettes; use of various types of smoking cessation strategies; dual use and often complete relapse to tobacco products. Conclusions: Patients with established CVD view e-cigarettes as a means of smoking cessation; however, many relapse to tobacco products or use both simultaneously. Further research is necessary regarding the role of e-cigarettes in smoking cessation in this high-risk group.